1998
DOI: 10.1259/bjr.71.849.10195004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the efficacy of dimeric and monomeric non-ionic contrast media (iodixanol vs iopromide) in urography in patients with mild to moderate renal insufficiency.

Abstract: Non-ionic dimers induce less diuresis than non-ionic monomers, resulting in increased opacification of the urinary tract in intravenous (i.v.) urography. This double blind, comparative, randomized, parallel trial compared the efficacy of iodixanol (non-ionic dimer) and iopromide (non-ionic monomer) in 100 patients with mild to moderate renal insufficiency (serum creatinine of 135 to 265 mumol l-1) who underwent i.v. urography. A total dose of 600 mgI kg-1 bw of iodixanol (320 mgI ml-1) or iopromide (300 mgI ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…However, it is believed that there is no difference in excretion speed from the blood between the two contrast media because the CT value of the aorta showed a similar TDC pattern in both groups and blood iodine concentration after one hour did not show a significant difference. In addition, according to the past reports that indicate there was no significant difference in the contrast effect except in the kidney between monomeric and dimeric contrast media [2,[9][10][11], and the reports of increasing urinary volume with the use of monomeric contrast media relative to dimeric contrast media [7,10], it is considered that the remarkable difference in the contrast effect in the kidney is mainly derived from the osmotic diuresis in the renal tubules. This means that, after passing the glomerulus, the monomeric contrast media, with high osmolarity, is diluted in the renal tubules because it receives greater influence of osmotic diuresis than dimeric contrast media by reason of its high osmolarity [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is believed that there is no difference in excretion speed from the blood between the two contrast media because the CT value of the aorta showed a similar TDC pattern in both groups and blood iodine concentration after one hour did not show a significant difference. In addition, according to the past reports that indicate there was no significant difference in the contrast effect except in the kidney between monomeric and dimeric contrast media [2,[9][10][11], and the reports of increasing urinary volume with the use of monomeric contrast media relative to dimeric contrast media [7,10], it is considered that the remarkable difference in the contrast effect in the kidney is mainly derived from the osmotic diuresis in the renal tubules. This means that, after passing the glomerulus, the monomeric contrast media, with high osmolarity, is diluted in the renal tubules because it receives greater influence of osmotic diuresis than dimeric contrast media by reason of its high osmolarity [6].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the osmolarity of the contrast media has no significant effect on the contrast study in most organs because the changes in iodine concentration in these organs are influenced mainly by tissue blood flow. On the other hand, in the kidney, which consists of blood vessels and renal tubules, the contrast effects are influenced by the osmolarity of the media because changes in iodine concentration are influenced by both renal blood flow and excretion of iodine to tubules [2,[9][10][11].…”
mentioning
confidence: 99%
“…In one trial iodixanol showed better filling and density of the calyces, more frequent detection of papillary blush, and better opacification of the renal pelvis than iopromide [46].…”
Section: Efficacymentioning
confidence: 99%
“…This has been utilized in a variety of studies (3)(4)(5)(6)(7)(8)(9). Some developments of this simple approach attempt to take into account changes in diagnoses that might arise as a result of the test.…”
mentioning
confidence: 99%